Analysing substitutions in recent World Cups and European Championships in male and female elite football – influence of new substitution rules - Wei, Xiaobin; Shu, Yang; Liu, JiaJun; Chmura, Paweł; Randers, Morten B.; Krustrup, Peter (Biology of Sport, 2024)
Substitutions play a key role in modern football and can substantially affect the physical and overall performance of a team, and the recent substitution rule changes are worth investigating. This study explored the characteristics of substitutions, including different substitution rules, game results, sex, competition stages, tournaments and penalty shoot-outs success rates. We analysed data from a total of 3,738 substitutions from the last 10 years (2013–2023) of European Championships and World Cups, both men’s and women’s games. Nonparametric tests and chi-square tests were used for statistical analysis with the significance level set at p < 0.05. With the 5-substitution rule, 48% more substitutions occurred compared to the 3-substitution rule (4.26±1.07 vs. 2.87±0.43, p < 0.05) with a slight increase in the average substitution time (70.6±14.3 vs. 69.2±14.6 min, p < 0.05), and 10% more substitutions in the men’s game compared to the women’s game ( p < 0.05). The timing of the firstsubstitution wasslightly different in the knock-outstage compared to group stage (59.8±14.7 vs. 57.2±13.3 min, p < 0.05), and the timing for the winning team and drawing team was later than for the losing team ( p < 0.05). A total of 13.2% goals were scored by substitutes, with no significant difference between the 5-substitution rule (15.9%) vs the 3 substition rule (12.5%) ( p > 0.05). Interestingly, substitute players had a lower success rate in penalty shoot-out compared to starters (61 vs. 74%, p < 0.05). Additionally, substitute player goal scorers entered the pitch later ( p < 0.05) in male games compared to female games and in knock-out stage games compared to group games. This study highlights the importance of substitution rules and timing in modern elite football matches. The timing of the first substitution, introduction of substitutes in knock-out stages, and a lower success rate of substitute players in penalty shoot-outs are crucial factors to consider. Coaches can use this information to make strategic substitution decisions to improve team performance.